Selective vulnerability of the intermediate retinal capillary plexus precedes retinal ganglion cell loss in ocular hypertension - Pitale, Priyamvada M.; Shen, Guofu; Sigireddi, Rohini R.; Polo-Prieto, Maria; Park, Yong H.; Gibson, Solomon E.; Westenskow, Peter D.; Channa, Roomasa; Frankfort, Benjamin J. (Frontiers in Cellular Neuroscience, 2022)
Glaucoma, a disease of retinal ganglion cell (RGC) injury and potentially devastating vision loss, is associated with both ocular hypertension (OHT) and reduced ocular blood flow. However, the relationship between OHT and the retinal capillary architecture is not well understood. In this project, we studied microvasculature damage in mice exposed to mild levels of induced OHT. Mild OHT was induced with the microbead model for 2 weeks. At this time point, some retinas were immunostained with CD31 (endothelium), Collagen IV (basement membrane), and RBPMS (RGCs) for z-stack confocal microscopy. We processed these confocal images to distinguish the three retinal capillary plexi (superficial, intermediate, and deep). We manually counted RGC density, analyzed vascular complexity, and identified topographical and spatial vascular features of the retinal capillaries using a combination of novel manual and automated workflows. Other retinas were dissociated and immunopanned to isolate RGCs and amacrine cells (ACs) for hypoxia gene array. RGC counts were normal but there was decreased overall retinal capillary complexity. This reduced complexity could be explained by abnormalities in the intermediate retinal capillary plexus (IRCP) that spared the other plexi. Capillary junction density, vessel length, and vascular area were all significantly reduced, and the number of acellular capillaries was dramatically increased. ACs, which share a neurovascular unit (NVU) with the IRCP, displayed a marked increase in the relative expression of many hypoxia related genes compared to RGCs from the same preparations. We have discovered a rapidly occurring, IRCP specific, OHT induced vascular phenotype that precedes RGC loss. AC/IRCP NVU dysfunction may be a mechanistic link for early vascular remodeling in glaucoma